Iscrizioni medievali nel territorio fiorentino fino al XIII secolo - Gramigni, Tommaso (Premio Ricerca «Città di Firenze», 2012)
Despite the interest that has always been shown towards Florence in the Middle Ages, to date no systematic catalogue has existed of the medieval epigraphic evidence from the Florentine area. The work presents a census of 122 inscriptions on stone material, dating from the sixth to eighth century, from the territory of the current province of Florence. It makes an analysis and comparison of their material, graphic and textual characteristics and recovers some evidence which was little known or had even been completely forgotten. The introduction to the catalogue, also accompanied by numerous reproductions, follows the developments and history of medieval epigraphy studies in Italy and attempts to make a summary of the actual graphical aspects of the writings under analysis.